CILI as a source of inspiration for ideas for crating work of fine art - Utama, Pande Komang Budhi Sastra; Setem, I Wayan; Kondra, I Wayan (Program Studi Seni Murni ISI Bali, 2025)
This report describes the creation of works of painting with the theme